DEVELOPMENT OF A MOTION AND SOUND SENSOR-BASED SMART TRASH CAN WITH A BUZZER NOTIFICATION SYSTEM - Rumahorbo, Daniel; Hasangapon Perapat, Gerhard; Khoiri Nasution, Aurela; Naufal, Ahmad; Arnita, Arnita (Computer Science Department, Malang National Institute of Technology, 2025)
Waste management remains a critical environmental challenge. This research aims to design and implement a prototype of a smart trash bin based on motion and sound sensors with an automatic notification system to improve efficiency and hygiene. The system utilizes an Arduino Uno microcontroller as the central control unit, integrated with two HC-SR04 ultrasonic sensors and a buzzer. The first sensor detects the user's hand movement to automatically open and close the lid via a servo motor, enabling a contactless process. The second sensor measures the waste level inside the bin; when the trash reaches full capacity, the system activates the buzzer as a local notification for cleaning personnel. The prototype was tested in a laboratory setting, and the results confirm that all components functioned optimally according to the design. The system successfully provides an innovative, practical, and efficient solution for smarter waste management, serving as an early implementation of appropriate technology that operates independently without an internet connection